Compound Selectivity and Target Residence Time of Kinase Inhibitors Studied with Surface Plasmon Resonance. Issue 4 (17th February 2017) - Willemsen-Seegers, Nicole; Uitdehaag, Joost C.M.; Prinsen, Martine B.W.; de Vetter, Judith R.F.; de Man, Jos; Sawa, Masaaki; Kawase, Yusuke; Buijsman, Rogier C.; Zaman, Guido J.R.
Abstract: Target residence time ( τ ) has been suggested to be a better predictor of the biological activity of kinase inhibitors than inhibitory potency (IC50 ) in enzyme assays. Surface plasmon resonance binding assays for 46 human protein and lipid kinases were developed. The association and dissociation constants of 80 kinase inhibitor interactions were determined. τ and equilibrium affinity constants ( K D ) were calculated to determine kinetic selectivity. Comparison of τ and K D or IC50 values revealed a strikingly different view on the selectivity of several kinase inhibitors, including the multi-kinase inhibitor ponatinib, which was tested on 10 different kinases. In addition, known pan-Aurora inhibitors resided much longer on Aurora B than on Aurora A, despite having comparable affinity for Aurora A and B. Furthermore, the γ/δ-selective PI3K inhibitor duvelisib and the δ-selective drug idelalisib had similar 20-fold selectivity for δ- over γ-isoform but duvelisib resided much longer on both targets. Graphical abstract: Highlights: Resource of on- and off-rates of important kinase inhibitor drug interactions Analysis of the binding of irreversible tyrosine kinase inhibitors in real time Known "pan"-Aurora kinase inhibitors reside longer on Aurora B than Aurora A. Idelalisib and duvelisib have same selectivity for δ- over γ-isoform PI3K.